Videoclipe e música: a experiência estética entra em cena na história - Passold, Gabriel (2021)
This work consists of twenty scenes constituted from the sharing of our aesthetic experience with some music and mainly with music videos, and aims to try an indisciplinary approach that associates the researcher’s perspectives with viewer/listener’s. The scenes are divided between four chapters that start from discussions about society, technology and freedom, in addition to a last part where we expose some scenes in a more experimental basis. In the first part, entitled Society, we show some academic perspectives with music and expose our relationship with the sources; we have a debate about the “real content” and the “ostentation”; we show a social thought among the rhymes, melodies and imagens of Filipe Ret’s words, we discussed academic criticism and our aesthetic experience with Anitta and also about artistic productions between information an entertainment. Then, we departed from Technology to talk about artistic productions between the “marketing” and “political”; about the sensoriality regimes of art from Sabotage; the anonymous and the explosion of language; music outside the boundaries between genres and nationalities; and we end with the scenes about sharing music on the internet ad with a reflection about the series Sense 8 and the aesthetic community. In the third part, Freedom, we discuss the works between living and surviving from the music video AmarElo, by Emicida; the multiple temporalities and the conception of other places in music videos; in addition to the relationship between dance and sexuality at the history of music and music videos. In the last part we titled: Experiencing music videos; the scenes have a more experimental character than the previous ones, and talk about fashion, art and publicity; seven music videos of the same Halsey song; about the aesthetic experience between the music and the music video; ending with some observations about the audiovisual album Lemonade, by Beyoncé.